UPAYA PENYELESAIAN HUKUM PRODUK MAKANAN OLAHAN HOME INDUSTRI CACAT PRODUKSI - Rusmiyah Rusmiyah (JURNAL LEGISIA, 2022)
Food is everything that comes from biological sources and water both processed and unprocessed, which is intended as food or drink for human consumption, including food additives, food raw materials, and other materials used in the process of preparing, processing, and or making food or beverages. Meanwhile, what is meant by food is food or drinks processed in a certain way or method with or without food additives. This research uses the normative method with a descriptive normative juridical approach with a statutory approach as the main source of legal material and literature, theory and various sources from online media as secondary legal material, which is associated with problems solving legal problems related to food. The consumer protection law in principle prioritizes the protection of the basic rights of consumers by increasing the awareness, ability, and independence of consumers to protect themselves; elevate the dignity and dignity of consumers by avoiding them from negative excesses due to the use of goods and / or services; improve the consumer protection system in choosing, determining and demanding rights as consumers; creating a consumer protection system that contains elements of legal certainty and information disclosure as well as access to information. Consumers of processed food industry products that are defective in production as aggrieved parties can file a claim for compensation through BPSK or through the courts. The settlement efforts through BPSK aim to: Reach an agreement on the form and amount of compensation, and/or, certain actions to guarantee that there will be no re-occurrence of losses suffered by consumers. If the dispute resolution efforts through BPSK are declared unsuccessful by one of the parties, a lawsuit can be filed through the court